Analysis of Sportsmanship’s Impact on FAFAGE Academy Sumedang Futsal Performance - Krisna Nafiul Ariyanto; Tedi Supriyadi; Entan Saptani (Journal Coaching Education Sports, 2026)
This study aimed to analyze the role of sportsmanship in improving the quality of futsal performance among athletes of FAFAGE Sumedang Academy. Sportsmanship is an essential value in sport that includes honesty, adherence to rules, respect for opponents and referees, and the ability to control emotions during competition. This study employed a qualitative approach with a case study design involving 18 participants, consisting of one coach and seventeen active athletes selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that sportsmanship played a significant role in enhancing the quality of futsal performance through the implementation of honesty and fair play, compliance with rules, emotional regulation, respect for referees’ decisions, and positive attitudes toward opponents. Emotional control and maintaining focus during matches emerged as the most dominant aspects influencing game quality. In addition, consistent sportsmanship coaching conducted by coaches through fair play education, discipline, and character development contributed to the formation of positive athlete behavior and supported team performance. The study also found that sportsmanship not only functions a moral value but also serves an important factor in improving technical performance, decision-making, teamwork, and concentration during matches. The novelty of this research lies in integrated examination of the relationship between sportsmanship and futsal performance through technical, psychological, and social dimensions within the context of youth athlete development in a futsal academy environment.